Increasing Use of Teleteaching - Gerald R. McKay (Journal of Applied Communications, 1972)
The telephone seems to be coming of age as a teaching technique in Cooperative Extension work in the United States. Whether it will take its place along with 16mm films, magnetic tapes, and publications or will itself be replaced by an even newer medium remains to be seen.